Experimental and Theoretical Studies of the Colloidal Stability of Nanoparticles−A General Interpretation Based on Stability Maps - Segets, Doris; Marczak, Renata; Schäfer, Stefan; Paula, Carolin; Gnichwitz, Jan-Frederik; Hirsch, Andreas; Peukert, Wolfgang (Acs Nano, 2011)
The current work addresses the understanding of the stabilization of nanoparticles in suspension. Specifically, we study ZnO in ethanol for which the Influence of particle size and reactant ratio as well as surface coverage on colloidal stability in dependence of the purification progress was investigated. The results revealed that the well-known zeta-potential determines not only the colloidal stability but also the surface coverage of acetate groups bound to the particle surface. The acetate groups act as molecular spacers between the nanoparticles and prevent agglomeration. Next to DLVO calculations based on the theory of Derjaguin, Landau, Verwey and Overbeek using a core shell model we find that the stability is better understood in terms of dimensionless numbers which represent attractive forces as well as electrostatic repulsion, steric effects, transport properties, and particle concentration. Evaluating the colloidal stability in dependence of time by means of UV-vis absorption measurements a stability map for ZnO is derived. From this map it becomes clear that the dimensionless steric contribution to colloidal stability scales with a stability parameter including dimensionless repulsion and attraction as well as particle concentration and diffusivity of the particles according to a power law with an exponent of -0.5. Finally, we show that our approach is valid for other stabilizing molecules like cationic dendrons and is generally applicable for a wide range of other material systems within the limitations of vanishing van der Weals forces in refractive index matched situations, vanishing zeta-potential and systems without a stabilizing shell around the particle surface.
Keywords: nanoparticles; stabilization; particle size; electrostatic; repulsion